(untitled) (Al-Qamar, 2018)
Abū Nu’ym al-Asfahānī has authored many books on various topics, especially on the subjects like classes, genealogy, history , and biography etc. One of them his well known book is " Maʻrifat al-Sahābah". This book is an encyclopedia on Sahabah’s life. The author has introduced four thousand two hundred and thirty five personalities in the book and has presented eight thousand one hundred and five Ahadīth and Āsār. This research paper covers the methodology of Abū Nu’ym al-Asfahānī that he adopted in his book Maʻrifat al-Sahābah, specially in narrating the Ahadīth. The author mentioned different types of Ahadīth but we cover some of them like traditions about Quranic verses and the circumstances in which they revealed , traditions of Dalāil al-Nubuwwah , traditions of Sahabāh relationship with Muhammad peace be upon him, traditions narrating rare events of Sīrah and tradition of letters written to different rulers. This research paper is expected to provide concise perception of Abu Abū Nu’ym al-Asfahānī methodology and his way of research in his work Maʻrifat al-Sahābah .